GPS Technology Implementation for Sangihe Islands' Movement Monitoring in 2017-2019 - Hilmiyati Ulinnuha; Dwi Lestari; Leni Sophia Heliani; Nurrohmat Widjajanti; Cecep Pratama; Parseno Parseno; Krishna Fitranto Nugroho (Jurnal Geospasial Indonesia, 2019)
Sangihe Islands belong to a complex tectonic area at the subduction of the Eurasian plate and the Philippine Sea. Sangihe subduction zones are complex subduction zone, so that there is a need for continuous movement monitoring. Previous research had been carried out to monitor movement of the Sangihe subduction zone, but no monitoring has been done in 2019. Therefore, this study aims to monitor movement of Sangihe subduction zones with the latest observation data.This study aims to obtain velocity of Sangihe Islands plate movement during 2017 to 2019. Observation was performed using 3 monitoring control points for 7 days in 2019. While observation data from 2017 to 2018 were obtained from previous studies. Observations was carried out using GNSS differential method technology. Loosely constrained of weighted parameter was performed in least square adjustment of GNSS data daily processing, while Kalman Filtering algorithm applied for combining multiyear GNSS data to estimate the velocity refer to ITRF 2014 using GAMIT/GLOBK.This study indicates that Sangihe Islands has horizontal movement to the Southeast with velocity vector of 1 to 2.16 cm/year. This results confirm the previous studies in that area.